NOVEL DRUGS IN FOLLICULAR LYMPHOMA - Giuseppe Rossi; Antonella Anastasia (Mediterranean Journal of Hematology and Infectious Diseases, 2016)
Follicular lymphoma(FL) is the most common indolent non-Hodgkin lymphoma and constitutes 15% to 30% of lymphoma diagnoses. The natural history of the disease is characterized by recurrent relapses and progressively shorter remissions with a median survival of 10yrs. The impossibility of a chieving a definite cure, have prompted investigations into the possible role of more effective and less toxic strategies with innovative therapeutic agents.